2020
DOI: 10.1186/s12889-020-08489-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abnormal glucose metabolism among adults attending an outpatient department at a tertiary referral hospital in Swaziland: a cross-sectional study

Abstract: Background: The exact prevalence of type 2 diabetes mellitus (T2DM) and pre-diabetes in Swaziland remains unknown. Estimates suggest that the prevalence rate of type 2 diabetes mellitus is between 2.5 and 6.0% in Swaziland. The disparity in these estimates is due to a lack of quality data but the prevalence of diabetes is increasing in Swaziland. This study estimates the prevalence of type 2 diabetes mellitus and pre-diabetes among patients in a tertiary hospital in Manzini, Swaziland. Methods: A cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In Eswatini, literature on DM in the population and DM-TB comorbidity is scarce with easily accessible data being estimates by WHO and International Diabetes Federation (IDF). 25 Available studies have centred on HIV-NCD comorbidity and developing effective integration models to address the increasing cases of NCDs among HIV patients. 26 A 2020 study on the prevalence of abnormal blood glucose metabolism in adults indicated a 3.9% prevalence of type 2 DM (T2DM) in adults who attended the outpatient department of a tertiary hospital but no data is available on associated comorbidities with TB or HIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eswatini, literature on DM in the population and DM-TB comorbidity is scarce with easily accessible data being estimates by WHO and International Diabetes Federation (IDF). 25 Available studies have centred on HIV-NCD comorbidity and developing effective integration models to address the increasing cases of NCDs among HIV patients. 26 A 2020 study on the prevalence of abnormal blood glucose metabolism in adults indicated a 3.9% prevalence of type 2 DM (T2DM) in adults who attended the outpatient department of a tertiary hospital but no data is available on associated comorbidities with TB or HIV.…”
Section: Introductionmentioning
confidence: 99%
“…In Eswatini, literature on DM in the population and DM-TB comorbidity is scarce with easily accessible data being estimates by WHO and International Diabetes Federation (IDF) 25. Available studies have centred on HIV-NCD comorbidity and developing effective integration models to address the increasing cases of NCDs among HIV patients 26.…”
Section: Introductionmentioning
confidence: 99%
“…In Eswatini, there has been a drastic increase in overweight and obesity rates over the past years, with women more overweight/obese than men [ 59 ]. Overweight and obesity have been found to be significant predictors of numerous NR-NCDs including type 2 diabetes mellitus, hypertension, cardiovascular disease, and certain cancers [ 1 , 60 , 61 ]. The increasing rates of overweight/obesity among WLHIV in rural households are disconcerting as they suggest an increased risk of NR-NCDs and further exacerbating challenges experienced by women in these communities [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obesity have been found to be significant predictors of numerous NR-NCDs including type 2 diabetes mellitus, hypertension, cardiovascular disease, and certain cancers [ 1 , 60 , 61 ]. The increasing rates of overweight/obesity among WLHIV in rural households are disconcerting as they suggest an increased risk of NR-NCDs and further exacerbating challenges experienced by women in these communities [ 60 , 61 ]. With an increasing prevalence of overweight and obesity in food insecure households, there is a need to re-evaluate current strategies and develop multi-level targeted interventions that include prevention of excessive weight gain among women, particularly those living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the examination procedures and the participants' characteristics has been provided elsewhere [16]. Briefly, 385 patients attending the OPD at Raleigh Fitkin Memorial Hospital in Manzini, Swaziland were included in the study.…”
Section: Methodsmentioning
confidence: 99%